2015
DOI: 10.1186/s12889-015-1540-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and mechanism for outcomes exploration of providing public health care in contract service in Rural China: a multiple-case study with complex adaptive systems design

Abstract: BackgroundThe Chinese government has increased the funding for public health in 2009 and experimentally applied a contract service policy (could be seen as a counterpart to family medicine) in 15 counties to promote public health services in the rural areas in 2013. The contract service aimed to convert village doctors, who had privately practiced for decades, into general practitioners under the government management, and better control the rampant chronic diseases. This study made a rare attempt to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Although many studies proved that the causal association between the public health expenditure and infant or child mortality [9,10], some studies well summarized China's experience on public health in 1949-1984 [3,16] and lessons in 1985-2002 [4,17], some studies assessed the effects of NEPHSP on service coverage and equity [14,[40][41][42][43][44][45][46][47][48], very few studies described China's financing strategies and mechanisms for the NEPHSP [34,35,41,43]. This study could be an important contribution to the exiting literature on evaluation of public health equalization in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies proved that the causal association between the public health expenditure and infant or child mortality [9,10], some studies well summarized China's experience on public health in 1949-1984 [3,16] and lessons in 1985-2002 [4,17], some studies assessed the effects of NEPHSP on service coverage and equity [14,[40][41][42][43][44][45][46][47][48], very few studies described China's financing strategies and mechanisms for the NEPHSP [34,35,41,43]. This study could be an important contribution to the exiting literature on evaluation of public health equalization in China.…”
Section: Discussionmentioning
confidence: 99%
“…The government also purchase the public health services by signing a contract with the private sector such as village doctors and the latter receive a modest subsidy for providing public health services associated with the package. The willingness of village doctors to provide public health services has been improved since the introduction of the package and a minimum subsidy, although village doctors do not find the subsidy to be sufficient remuneration for their efforts [42][43][44].…”
Section: Government Procurement Of Services and Public-private Partnementioning
confidence: 99%
“…This was similarly reported in other studies done in Sub Saharan Countries 10,11,15,23,29,31 whereby government was unable to send funds on time as agreed on SA. This was also reported by a study on SA conducted in China whereby provincial government did not send money to barefoot doctors as agreed 14 , thus affecting the effective implementation of SA as originally planned.…”
Section: Discussionmentioning
confidence: 88%
“…This was also reported in another study done in Chinaon evaluation and mechanism for outcomes exploration of providing public health care in contract service in Rural China whereby the provincial governements were not conducting supervision as agreed. 14 This study found that existence of guidelines and policies help to describe the procedures and ways that implementers of any plan need to follow in order to achieve certain results or outcomes of interest. This study found that the existence guidelines and policies on the implementation of SA is an opportunity for provision of guidance and direction by the government on how to implement, monitor and evaluate the progress of SA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation